ADVERTISING EDUCATIONAL INSTITUTIONS THROUGH ONLINE MEDIA DURING THE COVID-19 SITUATION: A CASE STUDY IN THE INTERNATIONAL COLLEGE OF KING MONGKUT’S UNIVERSITY OF TECHNOLOGY NORTH BANGKOK - Rawikul, Puntarika; Ammapuk, S; Labkim, N; Pewpong, T; Po, M (Proceedings of the International Conference on Education, 2022)
The coronavirus pandemic has slowed down the economy. People reduce their costs including a budget for education, therefore, educational institutions are undeniably affected. Moreover, the education industry has to adapt to the New Normal way of life. To survive in the market, they must rely on the Internet, not only for online studying but also as the main advertising channel. The researchers have realized this change. Thus, the mixed-method research was conducted with the aims of 1) to study how Thai and Cambodian students are open to online media, promotional videos, for deciding on a university and 2) to propose ways to produce online media, promotional videos, to make a university more famous. Dividing into two steps, firstly, the researchers collected the data via an online questionnaire from 400 students in the upper secondary schools and found that selecting a university, the samples were interested in details of basic information and admission, academic matters and job opportunities, university life and friendships, and international networks. The most popular channels providing the information were Facebook, YouTube, and websites. They also preferred video clips presented by current university students with real experiences. To be confirmed as an example, the researchers had created the video clips to promote the International College of KMUTNB based on the result and invited 12 participants to watch the videos and share their opinions through the in-depth interviews. Most of them agreed that the videos were helpful and relevant to their needs. In conclusion, this research result can be a benefit for advertising educational institutions.